Perspectives of telemedicine: a cross-sectional study among health care personnel - Aboregela, Adel M.; Hashish, Abdullah A.; Alqahtani, Masoud M.; Alqarni, Anas; Almuawi, Abdullah N.; Alamri, Mohannad S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Telemedicine is the remote delivery of medical services. There has yet to be sufficient data in our community on perspectives on telemedicine. Therefore, this study aimed to evaluate the perception and attitude of physicians and medical students in Bisha region toward telemedicine. Methods: A cross-sectional study was conducted among physicians in ten hospitals and primary health care centers in Bisha and medical students at the College of Medicine, University of Bisha, Saudi Arabia. A structured, self-administered online questionnaire with optional participation was distributed. Results: 239 responses were received with diverse distribution among different ages, genders, nationalities, occupations, and frequencies of daily technology use. The participants showed 60.3% acceptance of telemedicine, especially its helpfulness in transferring information among sectors. Various sociodemographic-dependent debates were retrieved regarding the viability of telemedicine approach, its integration ability, time and money saving, and flexibility. The frequency of personal computer use correlated positively with the participants’ perceptions and attitudes (p=0.001 and 0.003). A positive attitude was retrieved from 79.1% of participants, with readiness to obtain telemedicine training for better professional growth, especially in non-Saudi personnel. The lack of suitable equipment, patient satisfaction and compliance, weakness of the doctor-patient relationship, familiarity with technology, and extra load for physicians were the most prominent barriers mentioned by the participants. Conclusions: Meetings, training, and orientation programs still need to be scheduled for the general population, healthcare personnel, and information technologists to override the weaknesses in community awareness and telemedicine deficiencies and to get the benefit of this technology.